2022
DOI: 10.3390/bs12040114
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents for Older Adults’ Intention to Use Smart Health Wearable Devices-Technology Anxiety as a Moderator

Abstract: The increase in the demands for surveillance of chronic diseases, long-term care, and self-health management has allowed mobile smart health wearable devices to become products with greater business potential in past years. Wearable devices being able to be worn for long periods are the most suitable for 24-h weatherproof monitoring. Nevertheless, most technological products are not developed specifically for older adults. Older adults might be apprehensive and fearful about the use of technological equipment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
15

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
2
14
0
15
Order By: Relevance
“…Attitudes and subjective norms also had a positive effect on willingness. Consistent with previous studies [ 28 , 57 ], the greater the positive attitude, the higher the willingness to use. Thus, it is crucial for WHDs providers to gain positive comments from community residents by paying more attention to their health needs, and improving the value of WHDs related health services [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Attitudes and subjective norms also had a positive effect on willingness. Consistent with previous studies [ 28 , 57 ], the greater the positive attitude, the higher the willingness to use. Thus, it is crucial for WHDs providers to gain positive comments from community residents by paying more attention to their health needs, and improving the value of WHDs related health services [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study found that HA has a non-significant effect on the behavioral intentions of elderly adults to use wearable devices. Elderly users with health anxiety are willing to spend more time and effort finding all devices and tools that can assist in improving their health ( 67 ). Therefore, they will not only focus on whether the services provided by wearable devices are beneficial to their health but blame an external factor and seek other medical aids to escape from their current health problems and insecurities ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of ‘meaningful’ feedback about a patient’s health status can provide a sense of support, guidance and information, as well as giving reassurance to patients [ 41 ]. However, feedback by itself may also be an intrinsic motivator to sustained HM beyond any ‘clinically meaningful’ relevance of change in performance scores [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%